Analisa Kebutuhan Daya Mesin Pencetak Pelet Kapasitas 40 Kg/Jam - Rinjani, Bagus Sutra; Istiqlaliyah, Hesti (Jurnal Mesin Nusantara, 2022)
The problem faced by (our partners) fish farmers in Bangkok village is the high price and high demand for fish feed. This has resulted in fish cultivators in the village of Bangkok often experiencing losses in terms of time and energy. The fish cultivators there do not yet know how to make fish pellets independently, this is due to the high price of buying a pellet molding machine in the market and fish cultivators do not yet know the technology to design their own pellet printing machine. With the existing problems, the author and the team designed a fish pellet printing device and made sure that the tool used as little power as possible to help make it easier for fish farmers there. Fish pellet printing machine made using an electric motor with a rotation of 1400 rpm and a power of 1.5 HP, using a 1:40 ratio gearbox and found reduction data from a 35 rpm gear box, 12 rpm mixer and 12 rpm pellet printer. This machine is designed to produce 40 kg/hour.